Intermarriage and the Unhealthy Assimilation of Immigrant Descendants - Osea Giuntella (Institute for the Study of Labor (IZA), 2014)
This paper studies the effects of assimilation on the health of Hispanics in the US. I exploit a unique dataset of linked birth records and use ethnic intermarriage as a metric of acculturation. Intermarried Hispanics have a significantly higher socio-economic status than endogamously married Hispanics. Despite their higher socio-economic status and the positive socio-economic gradient in health, third-generation children of second- generation intermarried Hispanic women are more likely to have poor health at birth, even after I account for second-generation health at birth, employ only within-family variations in the extent of assimilation, and consider the endogeneity of intermarriage. These results do not appear to be driven by father's selectivity nor by individual unobservable characteristics associated with intermarriage. The children of intermarried natives do not receive the same "health penalty", nor do Hispanics intermarried to other ethnic groups. The intermarriage "health penalty" largely reflects the higher incidence of risky behaviors (e.g., smoking during pregnancy) among intermarried Hispanic women.
Keywords: I10; J15; 330; intermarriage; assimilation; birth outcomes; risky behaviors